NEW EMISSION STARS IN THE DARK REGIONS OF TAURUS AURIGA ORION INVESTIGATED BY JOY - IRIARTE ERRO, B; HARO, G; CHAVIRA, E (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1955)
New objects with Ha in emission were found on 28 objective prism plates taken with the Tonantzintla Schmidt camera in the Taurus-Auriga-Orion dark regions. The purpose of this investigation was firstly to determine the relation of the stars that exhibit t
BOL OBS TONAN TACUB
Keywords: NEW, EMISSION, STARS, DARK REGIONS, TAURUS, AURIGA, ORION, INVESTIGATED, JOY; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS